Examining the robustness of competing explanations of slow growth in African countries - Ronelle Burger; Stan du Plessis (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2006)
This research challenges previous findings regarding the robustness of the African growth dummy by expanding the list of variables to include those suggested by Easterly and Levine (1998) and Sachs and Warner (1997b). Using the Bayesian Averaging of Classical Estimates approach, this paper concludes that the African growth dummy does not appear to be robustly related to growth. This supports the interpretation that the presence of the African dummy in other studies results from misspecification. The paper also contributes to the debate on growth strategies for Africa by assessing the robustness of divergent perspectives offered in the recent literature.
Keywords: C11; O11; O40; 330; growth; Africa; model specification; robustness